2013
DOI: 10.2527/jas.2012-5903
|View full text |Cite
|
Sign up to set email alerts
|

Late gestational hyperprolactinemia accelerates mammary epithelial cell differentiation that leads to increased milk yield1

Abstract: The growth rate of piglets is limited by sow milk yield, which reflects the extent of epithelial growth and differentiation in the mammary glands (MG) during pregnancy. Prolactin (PRL) promotes both the growth and differentiation of the mammary epithelium, where the lactational success of pigs is absolutely dependent on PRL exposure during late gestation. We hypothesized that inducing hyperprolactinemia in primiparous gilts during late gestation by administering the dopamine antagonist domperidone (DOM) would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 33 publications
0
39
1
Order By: Relevance
“…Prolactin promotes both the growth and differentiation of the mammary epithelium for milk excretion, so higher blood serum prolactin concentration of sows may increase milk production and piglet growth (Vanklompenberg et al, 2013). This study showed a higher serum prolactin concentration in the lactating sows fed diet containing 5 -15% FSBM, inferring that milk excretion would be improved to increase growth and weaning survival rates for suckling piglets.…”
Section: Discussionmentioning
confidence: 60%
“…Prolactin promotes both the growth and differentiation of the mammary epithelium for milk excretion, so higher blood serum prolactin concentration of sows may increase milk production and piglet growth (Vanklompenberg et al, 2013). This study showed a higher serum prolactin concentration in the lactating sows fed diet containing 5 -15% FSBM, inferring that milk excretion would be improved to increase growth and weaning survival rates for suckling piglets.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, the total output of colostrum constituents was greater in high PRL/P4 than in low PRL/P4 sows. In sows, there is evidence that PRL stimulates lactose, protein, and lipid synthesis in lacteal secretions [15][16][17]. Furthermore, the number of PRL receptors in the mammary gland may be a limiting factor for PRL action.…”
Section: Effect Of P4 and Prl Concentrations On Colostrum Yield And Gmentioning
confidence: 97%
“…Immunohistochemistry for phosphorylated histone H3 (PH3), phosphorylated STAT5 (P-STAT5) and progesterone receptor (PR) was performed using procedures outlined by VanKlompenberg et al [23]. Sections of MG2, 3 and 5 (cranial to caudal) from each female were analyzed for PH3 and P-STAT5, while one section from MG3 was analyzed for PR.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Primers were synthesized by Sigma Life Science (St. Louis, MO) and PCR products sequence verified. Quantitative PCR reactions were performed using Fast SYBR Green master mix (Applied Biosystems, Foster City, CA), 200 nM of each primer and 0.4 L of cDNA, in duplicate, on a 7500 Fast Real-Time PCR System (Applied Biosystems) as previously described [23] with the following modifications. The annealing and extension temperatures used for each primer set are in Table 1.…”
Section: Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation